The Moderating Effect of Corporate Governance on the Relationship between Sustainability Performance and Financial Performance - Anita Anita; Agustini Fatmasari (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
This research is intendedto determine the influence of corporate governance on the relationship between sustainability performance and financial performance. The research method used is quantitative data obtained from the BEI (Indonesian Stock Exchange) website. The sample selection procedure used a purposive sampling method from 767 listed companies and only 53 companies met the criteria. Research results using software statistical program for social science(spss) and eviews 10 which proves that the size of the board of directors, CEO duality and female top board members have no effect on sustainability performance. The independence of the board of directors has a significant negative effect on sustainability performance. Furthermore, researchers also found that governance cannot moderate the relationship between sustainability and financial performance. Research data was collected using panel data regression analysis using time series data and cross-sectional data. The research findings conclude that the higher the level of governance in a company, the better it can pay attention to sustainability performance issues and can be used as a reference in making policies for the government and helps to use additional references regardingGRI (Global Reporting Initiative) disclosure.